(untitled) (Journal of Parents and Teachers, 2014)
This article presents the suspense film "The Clay Boy", in which, in early twentieth-century Argentina, a teenager is arrested for multiple crimes, including murders, tortures and fires. The vision of it affects the society, who, terrified, avoid at all costs leaving their children alone in the street, when, at present, violence and problems are not only there.